Modalidades y límites del estado de excepción en México: del liberalismo histórico a la Guerra Sucia - Rodríguez Kuri, Ariel (El Colegio de México, A.C., 2025)
In the historiography of the state of exception in Mexico, interpretations on its constitutional and political meaning have been based on an empirical foundation that has not been consolidated. This article acknowledges this weakness and works toward a gnoseological and historiographical revision of the state of exception, which was called the “suspension of guarantees” in the 1857 and 1917 constitutions. It discusses the weaknesses of the historiography when studying this phenomenon during the period of historic liberalism, the attempts to suspend guarantees by three postrevolutionary presidents (Carranza, Obregón and Ávila Camacho) and substitutes for the suspension of guarantees in secondary legislation, particularly the law on social dissolution, from its approval in 1941, the 1950 reform and its repeal in 1970, which occurred as a consequence of the 1968 student movement.